(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Maternity Early Obstetric Warning System (MEOWS) is a very useful emergency screening instrument to anticipate the morbidity and mortality of pregnant women. Primary Health Care as one of the first-level health facilities is expected to be able to use MEOWS as a way to reduce MMR. The purpose this study to know the factors associated with the use of MEOWS by Primary Health Care Midwives in Sleman Regency. Quantitative research with cross sectional design. The study population is an inpatient primary health care midwife in the Sleman Regency area with the sample of 68 midwives through proportional stratified random sampling techniques. Data collection is using questionnaires that have been tested for validity and reliability. Hypothesis testing uses the chi square test. There is a relationship between socialization (p<0.003) and training (p<0.000) about MEOWS with the use of MEOWS. There is no relationship between age (p<0.561), education level (p<0.69), length of work (p<0.716), knowledge level (p<0.576), and superior support (p<0.861) with the use of MEOWS. There is a relationship between socialization and training about MEOWS with the use of MEOWS by midwives of Primary Health Care in the Sleman Regency area.